The Impact of Data Analysis for Test Automation and Performance Using Big Data - Viji Vinod, Sudhakar Sengan, T.N.Aruna, Anu.P.Varghese, Vaidehi V, K. Sumathi (International Journal of Advanced Science and Technology, 2020)
Big Data is the consistent blast in the massive volume of information that produced, prepared, put away, and got to through applications that cope with a few simultaneous transactions of data, momentarily. Despite the truth that machine planners and creators are investigating better techniques to ace BD, Test Engineers and Architects are likewise now not a long route that starts confronting BTD. Testing organizations are no longer the slightest bit barred from taking care of massive data. This research examines the impact of check automation on software testers. Each one is necessary for the trade, for administrative processes, and the upcoming of the business. The future is not far, and it is tomorrow. The conclusion to this research suggests that people currently in manual software testing are in danger of being replaced. Keywords: Big Data, Test Model, Database, Data Validation, Data Analysis.